POSITIVE ASPECTS OF DISTANCE EDUCATION LEARNING - Verholias, Oleksandr Oleksandrovych; Verholias, Maiia Razmetivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Distance learning has become widespread in many countries around the world, including Ukraine, and its popularity is growing rapidly every year. As mentioned above, this method of training has become the main since the end of 2019 as a result of national quarantine to prevent the rapid spread of acute respiratory disease COVID-19. Modern society demands from higher education a new global task - the ability to provide access to higher education to a wider section of society, because for any country the degree of its economic and technological development, welfare of society is proportional to the average level of knowledge, skills and qualifications its active population. In Ukraine, distance education is extremely relevant. The reason for this success lies in the mass retraining and training of the maximum number of specialists throughout Ukraine with the use of minimal funds. Distance learning in Ukraine can fully develop in the presence of the following main components: regulatory framework; educational institutions of the contingent of students; qualified teachers; training programs and courses; appropriate material and technical base, development of quality criteria, etc.